ANALISIS PERJANJIAN PINJAM NAMA PADA JUAL BELI TANAH DITINJAU DARI UNDANG-UNDANG NOMOR 5 TAHUN 1960 Jo. PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 - Naiborhu, Yoshua Putra Dinata (2024)
Nominee agreement in practice, to have ownership rights to land in Indonesia, legal subjects who do not have the authority to own land with ownership rights, choose to use a nominee agreement. The nominee agreement is used by borrowing someone else's name just only to be recorded on the land certificate, not the owners. This legal research has 2 (two) objectives. First, to analyze and understand the validity and legal consequences of the nominee agreement of buying and selling lands in Indonesia. Second, to analyze dan to understand legal protection to land buyers wich buy lands with a nominee agreement. This research was conducted using normative legal research methods. This type of research is descriptive. Based on the results of research and analysis conducted, the authors obtained 2 (two) results of the discussion. First, UUPA Jo PP 24 of 97 does not recognize and does not accommodate the validity of the nominee agreement on the sale and purchase of land based on Article 19 Paragraph (1) UUPA Jo. Article 32 Paragraph (1) PP 24 of 97 which states that a certificate is a proof of right that applies as a strong means of proof. Article 5 of the UUPA also states that the agrarian law that applies to earth, water and space is customary law. Second, legal protection for land buyers is divided into two, preventive legal protection and repressive legal protection.